Factors Affecting Financial Distress: Evidence from Indonesia - Tirza Chrissentia; Liza Handoko (Milestone: Journal of Strategic Management, 2025)
This study analyzes the impact of various factors on financial distress in Indonesian companies, focusing on profitability, institutional ownership, firm size, firm age, interest expense, dividend payout, retained earnings, and the COVID-19 pandemic. The objective of the research was to understand the effects of those internal and external factors before crisis, during crisis and post crisis. Data from companies listed on the Indonesia Stock Exchange (excluding the financial sector) from 2013 to 2022. The numbers of the sample based on the criteria were 691 companies, which makes 6132 observation points in total as the sample for this research. The sample was analyzed using logistic regression to determine the relationship between these variables and financial distress. The study found that profitability significantly reduces the likelihood of financial distress, while firm size, firm age, high interest expenses, high retained earnings, and the COVID-19 pandemic significantly increase the likelihood of financial distress.  Based on the findings, this study analyzed the impact of a company's condition during a crisis and the effect of external factors on the probability of financial distress and its impact on the company. The study can be used as a basis for company planning under external pressure conditions, considering the possibility of future events like pandemics or other crises.